Effects of Diet on the Biochemical Properties of Limulus Amebocyte Lysate From Horseshoe Crabs in an Aquaculture Setting - Tinker-Kulberg, Rachel; Dellinger, Anthony; Brady, Terry E.; Robertson, Lee; Goddard, Melinda K. M.; Bowzer, John; Abood, Sarah K.; Kepley, Christopher; Dellinger, Kristen (Frontiers in Marine Science, 2020)
The Limulus amebocyte lysate (LAL) isolated from cells in the horseshoe crab (HSC) hemolymph is a critical resource for global biomedical and pharmaceutical quality control and sterility testing. Given the necessity of and limitations associated with wild capture, a conservational approach to LAL harvesting would benefit the medical community that relies on the raw material while helping ensure species viability. We posited that aquaculture and year-round collection represented a sustainable alternative for the production of LAL from a finite HSC cohort, thereby averting the impact of current practices on wild populations. Given the specter of captivity diseases linked to diet, such as panhypoproteinemia, this work, at the outset, focused on optimizing a feed formulation to ensure animal vitality. In turn, each preparation required evaluation with respect to effects on LAL, as well as vital HSC health markers, so as to meet or exceed industry requirements and establish a new supply chain paradigm. In this controlled husbandry study, we conducted three 8-week feeding trials and demonstrated a ∼7-fold LAL reactivity range among the HSC feed groups. Relative protein abundance patterns of HSC amebocyte clotting factors (i.e., Factor C, Factor B, and proclotting enzyme) were influenced by diet in particular, and the up-regulation of specific LAL factors correlated with enhanced reactivity. These results also cite the discovery that coagulation Factor C, the LPS-sensitive serine protease proenzyme, may be a phosphoprotein.